Analysis Of Generation Z’s Perception Towards Korean Food Buying Interest (Case Study; Korean Food Tteokbokki At Dookki Central Park Restaurant) - Rina Fitriana; Heru Suheryadi; Maisie Michaelia Kurniawan (Jurnal Multidisiplin Sahombu, 2025)
This research aims to determine whether the perceptions of generation Z have an influence on the intention to buy Korean food, especially Korean food tteokbokki at Dookki Central Park restaurant and to find out how big the influence is. This research used a descriptive quantitative approach, while the data were obtained through distributing questionnaires and observation. Generation Z’s perception has a big influence on the intention to buy Korean Food especially tteokbokki at Dookki Central Park restaurant.